6 min walk test is a strong independent predictor of death in outpatients with heart failure - Morten Grundtvig; Torfinn Eriksen-Volnes; Stein Ørn; Eva Kjøl Slind; Lars Gullestad (Norsk Forening for Epidemiologi, 2023)
The following paper is reprinted from ESC Heart Failure ESC Heart Failure 2020; 7: 2904-2911 Published online 17 July 2020 in Wiley Online Library (wileyonlinelibrary.com) DOI: 10.1002/ehf2.12900